TECHNOLOGIES FOR ENHANCING SPIRITUAL – EDUCATIONAL WORK IN INCREASING THE EFFICIENCY OF PEDAGOGICAL PROFESSIOANAL SKILLS (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
This article examines the strategic integration of innovative technologies into spiritual-educational work to significantly boost the professional competence of educators. It analyzes how methods like ICT integration, collaborative learning, and axiological (value-oriented) approaches foster not only intellectual but also moral, ethical, and spiritual maturity in teachers. The core argument is that technologically supported spiritual education develops key pedagogical skills—including communication, ethical leadership, and self-regulation—making the educational process more holistic and effective in preparing morally responsible citizens.